Serum zinc level in vitiligo: A case-control study - Mina Mirnezami; Hoda Rahimi (Wolters Kluwer Medknow Publications, 2018)
Background: Vitiligo is characterized by the idiopathic destruction of melanocytes, probably of autoimmune etiology, that results in depigmented patches of skin and mucosal surfaces. Oxidative stress may contribute to the pathogenesis of vitiligo. Zinc, a trace element with antiapoptotic properties, plays a major role in the process of melanogenesis and elimination of free radicals. The present study was conducted with the aim of comparing serum zinc levels in patients with vitiligo and in normal controls. Materials and Methods: In this case-control study, we studied 103 patients with vitiligo and 103 healthy sex-and age-matched controls. Serum zinc levels were measured in these two groups using atomic absorption spectrophotometry and compared with each other. Results: The mean serum zinc level was 92.1 mcg/dl in the focal vitiligo, 81.3 mcg/dl in the generalized vitiligo, and 91.8 mcg/dl in the control group. A significant difference in serum zinc levels was observed between the patients with generalized vitiligo and the controls. Lower serum zinc levels were also correlated with longer duration of the disease. Furthermore, a negative relationship was found between serum zinc level and age of patients with vitiligo. Conclusion: Serum zinc level is low in patients with generalized vitiligo. In these patients, serum zinc level is in negative correlation with patient's age and disease duration.